Mineral Inversion Approach to Improve Ahdeb Oil Field's Mineral Classification - Usama Alameedy; Ghanim Farman; Haider Al-Tamemi (Iraqi Geological Journal, 2023)
Knowledge of the mineralogical composition of a petroleum reservoir's formation is crucial for the petrophysical evaluation of the reservoir. The Mishrif formation, which is prevalent in the Middle East, is renowned for its mineralogical complexity. Multi-mineral inversion, which combines multiple logs and inversions for multiple minerals at once, can make it easier to figure out what minerals are in the Mishrif Formation. This method could help identify minerals better and give more information about the minerals that make up the formation. In this study, an error model is used to find a link between the measurements of the tools and the petrophysical parameters. An error minimization procedure is subsequently applied to determine the optimal solution. The quality curve is useful for assessing the model's reliability and data depth. Gamma rays and traditional logs both show that calcite and dolomite are the most common matrix minerals in the Mishrif Formation. The clay minerals present in the formation are smectite, illite, and glauconite. Accurate detection of mineral composition resulted in improved identification of fluid content, particularly free and bound water saturation, and, by extension, hydrocarbon saturation.